Morphometric and molecular analysis of two distinct forms of Pseudocrossidium crinitum - Watson, Julia (Department of Biological Sciences, 2017)
Two distinct forms of Pseudocrossidium crinitum (Bryophyta) exist- a form with a white hair point on the leaf, and one with a yellow hair point on the leaf. The white and yellow forms exist in similar areas, but the yellow hair point form is found on its own in arid areas. In this paper we analyse 16 morphometric variables and chloroplast and nuclear DNA molecular information to determine whether Pseudocrossidium crinitum should be separated into two species based on morphological differences. We use ANOVA, Principal components analysis and cluster analysis to analyse the morphometric data. Four significantly different morphological differences were found between the two forms. Five haplotypes were revealed from 8 samples, with only one haplotype shared amongst them. Two samples from the Cedarburg exhibit highly different DNA to the rest of the samples. Although genetic sampling was not large enough on which to base significant conclusions, we find that the two forms - are morphologically differentiated enough to separate Pseudocrossidium crinitum into two species.